Solve : 3 (2x + 1) -2 (x - 5) -5 (5 - 2x) = 16

0 votes
1 view
asked Jul 11 in Class VI Maths by aditya23 (-2,193 points)

Solve : 3 (2x + 1) -2 (x - 5) -5 (5 - 2x) = 16

Please log in or register to answer this question.

1 Answer

0 votes
answered Jul 11 by muskan15 (-3,451 points)

3 (2x + 1) -2 (x - 5) -5 (5 - 2x) = 16

⇒ 6x + 3 – 2x + 10 – 25 + 10x = 16

⇒ 6x – 2x + 10x + 3 + 10 – 25 = 16

⇒ 16x – 2x + 13 – 25 = 16

⇒ 14x – 12 = 16 ⇒ 14x = 16 + 12 = 28

⇒ x = 28/14 = 2

∴ x = 2

Related questions